Intrauterine programming mechanism for hypercholesterolemia in prenatal caffeine‐exposed female adult rat offspring. Issue 10 (2nd May 2018) - Xu, Dan; Luo, Hanwen W.; Hu, Wen; Hu, Shuwei W.; Yuan, Chao; Wang, Guihua H.; Zhang, Li; Yu, Hong; Magdalou, Jacques; Chen, Liaobin B.; Wang, Hui
ABSTRACT: Clinical and animal studies have indicated that hypercholesterolemia and its associated diseases have intrauterine developmental origins. Our previous studies showed that prenatal caffeine exposure (PCE) led to fetal overexposure to maternal glucocorticoids (GCs) and increased serum total cholesterol levels in adult rat offspring. This study further confirms the intrauterine programming of PCE‐induced hypercholesterolemia in female adult rat offspring. Pregnant Wistar rats were intragastrically administered caffeine (30, 60, and 120 mg/kg/d) from gestational day (GD)9 to 20. Female rat offspring were euthanized at GD20 and postnatal wk 12; several adult rat offspring were additionally subjected to ice‐water swimming stimulation to induce chronic stress prior to death. The effects of GCs on cholesterol metabolism and epigenetic regulation were verified using the L02 cell line. The results showed that PCE induced hypercholesterolemia in adult offspring, which manifested as significantly higher levels of serum total cholesterol and LDL cholesterol (LDL‐C) as well as higher ratios of LDL‐C/HDL cholesterol. We further found that the cholesterol levels were increased in fetal livers but were decreased in fetal blood, accompanied by increased maternal blood cholesterol levels and reduced placental cholesterol transport. Furthermore, analysis of PCE offspring in the uterus and in a postnatal basal/chronic stress state and the results of in vitro experiments showed that hepatic cholesterol metabolism underwent GC‐dependent changes and was associated with cholesterol synthase via abnormalities in 3‐hydroxy‐3‐methylglutaryl‐CoA reductase (HMGCR) histone acetylation. We concluded that, to compensate for intrauterine placentally derived decreases in fetal blood cholesterol levels, high intrauterine GC levels activated fetal hepatic CCAAT enhancer binding protein α signaling and down‐regulated Sirtuin1 expression, which mediated the high levels of histone acetylation (via H3K9ac and H3K14ac) and expression of HMGCR. This GC‐ dependent cholesterol metabolism programming effect was sustained through adulthood, leading to the occurrence of hypercholesterolemia.—Xu, D., Luo, H. W., Hu, W., Hu, S. W., Yuan, C., Wang, G. H., Zhang, L., Yu, H., Magdalou, J., Chen, L. B., Wang, H. Intrauterine programming mechanism for hypercholesterolemia in prenatal caffeine‐exposed female adult rat offspring. FASEB J. 32, 5563–5576 (2018). www.fasebj.org